Assessing the Impact of Tourist Incivility, Job Satisfaction and Job Satisfaction on Trekking Guides Vocational Commitment - Dulal, Mandip; Karki, Bikram (KIC International Journal of Social Science and Management, 2024)
In the dynamic hospitality industry, employees engage deeply with customers, often becoming the organization’s face. This study investigates the influence of tourist incivility, job stress, and job satisfaction on the vocational commitment of trekking guides. Using a quantitative research approach with a descriptive and correlational design, the study explores these relationships through hypotheses derived from existing literature. Out of 384 Participants, primarily male (96.67%) and aged 26-35 years (57%), were recruited via convenience sampling from diverse geographical locations. The results reveal significant positive correlations between job satisfaction factors (JSF) and vocational commitment (VC) (r = .267, p <.01), job stress (JS) and VC (r = .243, p < .01), and tourist incivility (TI) and VC (r = .490, p < .01). The coefficient of determination (R² = 0.374) indicates that 37.4% of the variation in vocational commitment is explained by these predictors. ANOVA results (F = 58.966, p = 0.000) confirm the significance of the model. Regression analysis demonstrates that job satisfaction (β = 0.121, t = 3.347, p < .01), positively and job stress (β = -0.065, t = -4.550, p < .01), and tourist incivility (β = -0.300, t = -6.617, p < .01) negatively and significantly affect vocational commitment. The results show how tourist behavior, job worries, job satisfaction and commitment to the profession interact in trekking guides’ lives. This study points out that taking care of these issues will help employees feel better and more committed which benefits both the industry and its workers.